Methodology for Study of Rockfalls in Urban Areas – Computer Modeling and Mitigation in Algodonales, Spain - Pardo, Juan Manuel; Galera, Jose Miguel; Mulas, Joaquin (Geomatics and Environmental Engineering, 2024)
Rockfalls in urban areas can cause significant damage. Without direct observation, it is difficult to reconstruct the specific details of an event. The study of rockfalls requires analyses of the source areas, slope parameters, blocks characteristics (size, shape, and mass), and the likely movements of independent blocks along their trajectories (free-falling, rolling, sliding, and rebounding). This article will propose a feasible methodology for the study of rockfalls based on identifiable parameters, conditioning factors (geology, geomorphology, geomechanical, hydrogeology, climate, and biology), and triggering factors (climate and dynamic loads). This article proposes the use of modeling programs to facilitate rockfall research and data management. The study of conditioning factors allows researchers to state several coefficients (restitution, surface roughness, rolling resistance, and friction) that one inputs into a modeling program, allowing researchers to obtain the representative results that are needed to design effective remedial measures. The methodology has been successfully applied to the urban area of Algodonales (Province of Cádiz, Spain).